Experimental alcoholism and pathogenesis of prostatic diseases in UChB rats - Candido, Eduardo Marcelo; Fabrega Carvalho, Cesar Alexandre; Martinez, Francisco Eduardo; Alves Cagnon, Valeria Helena (Elsevier B.V., 2007)
Previous studies have shown that long-term alcohol treatment has negative effects on prostatic stromal-epithelial interaction. Thus, the aim of the present study was to analyze the histochemical, immunohistochemical and ultrastructural alterations that occur in the prostatic stroma and epithelium of rats submitted to chronic alcohol ingestion and alcohol abstinence, as well as to establish the relationship between these changes and prostatic diseases. Thirty male rats (10 Wistar and 20 UChB rats) were divided into three experimental groups: the control group received tap water, the alcoholic group received ethanol diluted to 10 degrees G.L. for 150 days, and the abstinent group received the same liquid diet as the alcoholic group up to 120 days of treatment and only tap water for 30 days thereafter. At the end of treatment, all animals were sacrificed and the ventral lobe of the prostate was removed and processed for histochemical, immunohistochemical and ultrastructural analyses. In addition, plasma testosterone levels were measured. The results showed, prostatic intraepithelial neoplasia, infolding of the epithelium towards the stroma, stromal hypertrophy and the presence of inflammatory cells in alcoholic animals. In the abstinent group, alterations were noted mainly in the stromal area. In conclusion, ethanol triggers alterations in prostatic epithelial and stromal compartments, affecting the stromal microenvironment and predisposing the organ to pathological processes. (C) 2006 International Federation for Cell Biology. Published by Elsevier Ltd. All rights reserved.
Keywords: alcoholism; UChB rat; prostate; stromal-epithelial interaction; morphology